2017
DOI: 10.1021/acsami.7b06968
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Stimuli-Driven Facile Metal-Free Hydrogen Evolution from Pyrene-Porphyrin-Based Crystalline Covalent Organic Framework

Abstract: A [2 + 2] Schiff base type condensation between 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (TAP) and 1,3,6,8-tetrakis (4-formylphenyl) pyrene (TFFPy) under solvothermal condition yields a crystalline, quasi-two-dimensional covalent organic framework (SB-PORPy-COF). The porphyrin and pyrene units are alternatively occupied in the vertex of 3D triclinic crystal having permanent microporosity with moderately high surface area (∼869 m g) and promising chemical stability. The AA stacking of the monolayers give a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
153
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(157 citation statements)
references
References 57 publications
4
153
0
Order By: Relevance
“…It was shown that the new catalyst was efficient in catalyzing HER with a remarkably low onset overpotential of ≈50 mV, which is the lowest reported overpotential ever for any types of COFs (Figure b.) in acidic solution . After 500 cycles in the potential range 0.2 to −0.5 V vs. RHE at a scan rate of 100 mV s −1 , no loss of activity was observed in terms of both onset potential and current density at different potentials.…”
Section: Her Catalysts For Hydrogen Productionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was shown that the new catalyst was efficient in catalyzing HER with a remarkably low onset overpotential of ≈50 mV, which is the lowest reported overpotential ever for any types of COFs (Figure b.) in acidic solution . After 500 cycles in the potential range 0.2 to −0.5 V vs. RHE at a scan rate of 100 mV s −1 , no loss of activity was observed in terms of both onset potential and current density at different potentials.…”
Section: Her Catalysts For Hydrogen Productionmentioning
confidence: 88%
“…However, the poor stability in water has limited most of them in large‐scale use. Recently, Bhunia and co‐workers synthesized a crystalline, quasi‐2D COF (SB‐PORPy‐COF) ( Figure a) through 5,10,15,20‐tetrakis(4‐aminophenyl)porphyrin (TAP) and 1,3,6,8‐tetrakis (4‐formylphenyl) pyrene (TFFPy) under solvothermal condition . This is the first metal‐free COF‐based electrocatalyst for electrocatalytic hydrogen evolution.…”
Section: Her Catalysts For Hydrogen Productionmentioning
confidence: 99%
“…Anirban Pradhan's group first took advantageo fp yrene-porphyin-based crystalline COFs as electrocatalysts to drive HER;h owever,t he overpotential at 5mAcm À2 is 380 mV and the Ta fel slope is 116mVdec À1 ,w hich is unsatisfactory for HER. [18] High thermostable covalent triazine frameworks( CTFs) as at ypical representative of COFs was synthesized using ah igh-temperature ionothermal method, the intrinsic aromatic nitrogen-rich and conterminous triazine unit (ÀC=NÀ,Ncontent calculated is 8.5 %) would be facile for charge transfer and provide additional actives ites for HER. [19,20] With this perspective, more stable CTFs seem to be an attractive catalyst carrier forl oading of nanoparticles owing to its excellent stabilityi ns trongly acidic media and give potentialelectrocatalyticactivity for HER.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen is an ideal green fuel with high energy density and heat conversion efficiency. It is often obtained by electrolysis of water under the action of catalyst, but these catalysts are often precious metals, which greatly increases the preparation cost . Therefore, it is necessary to develop new catalysts with low cost.…”
Section: Electrochemical Applications Of 2d Mof/cof Nanosheetsmentioning
confidence: 95%